Clinician treatment choices for post-traumatic stress disorder (PTSD) - Ambassadors survey of psychiatrists in 39 European countries - Kuzman, Martina Rojnic (2024)
Background: Considering the recently growing number of potentially traumatic events and stressors in Europe (i.e. war in Ukraine, COVID-19 pandemic, refugee waves), the European Psychiatric Association (EPA) undertook a study to investigate clinicians' treatment choices for Post-Traumatic Stress Disorder (PTSD). Results: The case-based analysis included 611 participants, who correctly classified the vignette as a case of PTSD, from Central and Eastern Europe, CEE (n=279), Southern Europe, SE (n=92), Northern Europe, NE (n=92) and Western Europe, WE (N=148). The majority would use antidepressants (82%), with sertraline being the most preferred one. Benzodiazepines and antipsychotics were significantly more frequently recommended by participants from CEE (33% and 4%, respectively), compared to participants from NE (11% and 0%) and SE (9% and 3%). A narrow majority (52%) of clinicians recommended trauma-focused CBT and 35% psychoeducation, irrespective of their origin. In the latent class analysis, we identified four distinct „profiles“of clinicians. In class 1 (N=367, 60.1%) psychiatrists would less often recommended any antidepressants. In Class 2 (N=65, 10.6%) clinicians would recommend trazodone and prolonged exposure therapy. In Class 3 (N=128, 21.0%) they more frequently propose mirtazapine and Eye Movemente Desensitization Reprocessing (EMDR) therapy. In Class 4 (N=, %), clinicians propose different antidepressants, benzodiazepines, anticonvulsants and cognitive processing therapy. Half of all participants in each region (50.1 %) stated they do not adhere to recognized treatment guidelines. Conclusions: Clinicians' decisions for PTSD are broadly similar among European psychiatrists, but do not fully comply with current clinical guidelines. Regional differences suggest the need for more dialogue and educational efforts to harmonize practice across Europe and promote the use of guidelines.